Dalton's Lymphoma as a Murine Model for Understanding the Progression and Development of T-Cell Lymphoma and Its Role in Drug Discovery - Raj Kumar Koiri; Aditi Mehrotra; Surendra Kumar Trigun (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2017)
Mouse models are irreplaceable tools for the study of carcinogenesis and the availability of rodent models have enabled rational screening of drugs. Hematological malignancies have been extensively studied in mouse models and broad range of lymphoid neoplasms has been reported in laboratory mice, occurring either spontaneously or after induction with radiation, chemicals or infection of newborn mice with leukemogenic viruses. Lymphomas are tumors that generally respond well to traditional therapies such as chemotherapy and radiotherapy. Dalton's lymphoma is a transplantable T-cell lymphoma of spontaneous origin in thymus of murine host and has emerged as an interesting model for cancer research, because of its usefulness in pre-clinical system for evaluating new or known drugs in the treatment of various cancers and in drug discovery development process.